Liver: collateral vascularization following induced ischemia by crossed clamping of the thoracic aorta - Oliveira, João César Dias; Raiser, Alceu Gaspar; Guimarães, Luciana Dambrósio; Faria, Renato Xavier; Hipler, Ricardo Alexandre (Brazilian Journal of Veterinary Research and Animal Science, 1999)
The visual observation and identification of the vessels that irrigate the corporal tissues is greatly facilitated by using special staining dyes and vessel distenders, or by using a positive vascular contrast solution. In this research, lateral intercostal thoracotomy was performed on the eighth intercostal space in the left side of 22 dogs followed by clamping of thoracic aorta ± 1 cm cranial to the diaphragm. Ten dogs were then injected with the gelatin/aniline mixture, and the other 12 dogs were given a positive vascular contrast solution. In summary, following clamping of the thoracic aorta, arteries that irrigate the diaphragm, but not the liver, were identified.